1984
DOI: 10.2307/3429808
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Cadmium-Induced Health Effects in Rabbits

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Human evidence, however, remains inconsistent: some authors [4][5][6] have observed that less severe renal tubular damage is reversible; others [7][8][9] have reported that, according to their experience, progression is the rule. In addition, there is only limited data available from animal experiments involving long-term oral exposure [10,11].Metallothioneins (MTs) have attracted much attention in studies of Cd toxicity since their isolation from the equine renal cortex more than 50 years ago (reviewed by Nordberg [12]). MTs comprise a family of low molecular mass (6-7 kDa) stress proteins incorporating a high content of cysteine and divalent metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human evidence, however, remains inconsistent: some authors [4][5][6] have observed that less severe renal tubular damage is reversible; others [7][8][9] have reported that, according to their experience, progression is the rule. In addition, there is only limited data available from animal experiments involving long-term oral exposure [10,11].Metallothioneins (MTs) have attracted much attention in studies of Cd toxicity since their isolation from the equine renal cortex more than 50 years ago (reviewed by Nordberg [12]). MTs comprise a family of low molecular mass (6-7 kDa) stress proteins incorporating a high content of cysteine and divalent metals.…”
mentioning
confidence: 99%
“…Human evidence, however, remains inconsistent: some authors [4–6] have observed that less severe renal tubular damage is reversible; others [7–9] have reported that, according to their experience, progression is the rule. In addition, there is only limited data available from animal experiments involving long‐term oral exposure [10,11].…”
mentioning
confidence: 99%